2018
DOI: 10.4322/2526-8910.ctoao1633
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Do Repertório De Habilidades Sociais De Usuários De Substâncias Psicoativas Em Tratamento

Abstract: Introduction: Mental and behavioral disorders due to the use of substances is a serious public health problem. Deficit in social skills can be considered a risk factor at the beginning or continuity of use. Objective: To evaluate the repertoire of social skills of users of multiple and varied psychoactive substances being treated at the Center for Psychosocial Care in Alcohol and Drugs. Method: The sample was composed of individuals diagnosed with Substance-related Disorder undergoing treatment at the Center f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Data from the Brazilian literature suggest there is concomitant use of several substances in several different age groups. 22,23 Another study with patients hospitalized due to use of substances found that most participants reported using multiple substances such as cannabis, alcohol, and crack/cocaine. 24 The results of this study suggest that adults living alone and consuming alcohol jointly with cannabis tend to report higher rates of impulsivity.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the Brazilian literature suggest there is concomitant use of several substances in several different age groups. 22,23 Another study with patients hospitalized due to use of substances found that most participants reported using multiple substances such as cannabis, alcohol, and crack/cocaine. 24 The results of this study suggest that adults living alone and consuming alcohol jointly with cannabis tend to report higher rates of impulsivity.…”
Section: Discussionmentioning
confidence: 99%